login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

A306290
a(n) = 1/(Integral_{x=0..1} (x^3 - x^4)^n dx).
2
1, 20, 252, 2860, 30940, 325584, 3364900, 34337160, 347103900, 3483301360, 34754081648, 345120260940, 3413758188932, 33655718658800, 330869721936600, 3244839440755920, 31754250910172700, 310165459118369712, 3024542552887591120, 29449493278116018800, 286360607519186119920
OFFSET
0,2
LINKS
Necdet Batir, On certain series involving reciprocals of binomial coefficients, Journal of Classical Analysis, Vol. 2, No. 1 (2013), pp. 1-8.
FORMULA
a(n) = 1/Beta(3*n+1,n+1) = (4*n+1)!/(n! * (3*n)!).
a(n) = Sum_{k = 0..n} (-1)^(n+k) * (3*n + 2*k + 1)*binomial(3*n+k, k). This is the particular case m = 1 of the identity Sum_{k = 0..m*n} (-1)^k * (3*n + 2*k + 1) * binomial(3*n+k, k) = (-1)^(m*n) * (m*n + 1) * binomial((m+3)*n+1, 3*n). - Peter Bala, Nov 02 2024
From Amiram Eldar, Dec 09 2024: (Start)
a(n) = (4*n + 1) * binomial(4*n, n) = A016813(n) * A005810(n).
Formulas from Batir (2013):
Sum_{n>=0} 1/a(n) = f(c) = 1.05435362585114283076..., where f(x) = (x*(x^2-1)/(2*(2*x^2+1))) * log(abs((x+1)/(x-1))) + ((x-1)*(x^3+1)/(4*x*(2*x^2+1))) * sqrt(x/(x-2)) * (arctan(sqrt(x/(x-2))) + arctan(((3-x)/(x+1))*sqrt(x/(x-2)))) + ((x+1)*(x^3-1)/(4*x*(2*x^2+1))) * sqrt(x/(x+2)) * (arctan(((x+3)/(x-1))*sqrt(x/(x+2))) - arctan(sqrt(x/(x+2)))), and c = sqrt(1 + (16/sqrt(3))*cos(arctan(sqrt(229/27))/3)).
Sum_{n>=0} (-1)^n/a(n) = f(d) = 0.953648123517883351708..., where f(x) is defined above, and d = sqrt(1 + 16*(2/(3*(9+sqrt(849))))^(1/3) - 2*(2/3)^(2/3)*(9+sqrt(849))^(1/3)). (End)
MATHEMATICA
Table[1/Beta[3*n+1, n+1], {n, 0, 20}]
PROG
(PARI) vector(20, n, n--; (4*n+1)!/(n!*(3*n)!))
(Magma) [Factorial(4*n+1)/(Factorial(n)*Factorial(3*n)): n in [0..20]];
(Sage) [1/beta(3*n+1, n+1) for n in range(20)]
(GAP) List([0..30], n -> Factorial(4*n+1)/(Factorial(n)*Factorial(3*n)));
CROSSREFS
KEYWORD
nonn,easy
AUTHOR
G. C. Greubel, Feb 03 2019
STATUS
approved